Endovascular treatment of pseudoaneurysms with electrolytically detachable coils. - Lempert, T E; Halbach, V V; Higashida, R T; Dowd, C F; Urwin, R W; Balousek, P A; Hieshima, G B (American Journal of Neuroradiology, 1998)
PURPOSE We describe the clinical presentation, angiographic findings, and clinical outcome in a group of patients with pseudoaneurysms treated by a new endovascular technique using Guglielmi electrolytically detachable platinum coils (GDCs).METHODS We retrospectively reviewed the angiographic and clinical findings in a series of 11 patients with pseudoaneurysms occurring in a variety of locations: seven in the cavernous carotid artery, one in the petrous carotid artery, two in the anterior cerebral artery, and one in the cervical vertebral artery.RESULTS All aneurysms were cured with GDC embolization. The only complication was a branch occlusion, which resolved with heparinization and produced no clinical sequelae.CONCLUSION Pseudoaneurysms can be safely and effectively treated by embolization with GDCs. Consideration needs to be given to the anatomic location of the pseudoaneurysm and the acuity of onset. Treatment efficacy may by improved if there are bony confines around the aneurysm or if therapy takes place in the subacute period, when the wall of the pseudoaneurysm has matured and stabilized.